2018
DOI: 10.1016/j.amjsurg.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in surgical outcomes of patients with Inflammatory Bowel Disease

Abstract: Black patients are at increased risk of post-operative DSM following surgery for IBD. The elevated rates of DSM are not explained by traditional risk factors like obesity, ASA class, emergent surgery, or stoma creation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 32 publications
6
12
0
Order By: Relevance
“…Even after multivariable analysis, rates of extended HLOS were between 15% and 20% higher for African‐Americans and ‘Others’. These data are indirectly supported by previous studies such as that of Gunnells et al , who showed that African‐American patients with IBD have higher rates of 30‐day readmission after elective surgery, and Montgomery et al , who reported that African‐American patients with IBD undergoing surgery had significantly higher complication rates even after multivariable analysis.…”
Section: Discussionsupporting
confidence: 79%
“…Even after multivariable analysis, rates of extended HLOS were between 15% and 20% higher for African‐Americans and ‘Others’. These data are indirectly supported by previous studies such as that of Gunnells et al , who showed that African‐American patients with IBD have higher rates of 30‐day readmission after elective surgery, and Montgomery et al , who reported that African‐American patients with IBD undergoing surgery had significantly higher complication rates even after multivariable analysis.…”
Section: Discussionsupporting
confidence: 79%
“…Similar findings were noted in another study wherein Black patients were noted to have 38% increased odds of major complication after IBD surgery compared with other racial and ethnic groups [32]. No racial differences in postoperative mortality were noted similar to what was seen in other studies [30,32,34].…”
Section: Disparities In Surgical Outcomessupporting
confidence: 86%
“…Another study found that Black, Hispanic and Asian IBD patients had a longer length of stay after IBD surgery compared with white IBD patients. In the study, Black patients had an increased likelihood of bleeding requiring transfusion, sepsis and renal insufficiency compared with white patients [34]. Similar findings were noted in another study wherein Black patients were noted to have 38% increased odds of major complication after IBD surgery compared with other racial and ethnic groups [32].…”
Section: Introductionsupporting
confidence: 79%
“…In a separate evaluation of data from National Surgical Quality Improvement Program, AA patients had an increased risk of death and serious morbidity after surgery for IBD, even after adjustments for potential confounders, such as age, sex, time to operation, smoking status, and obesity. 69 Enhanced recovery after surgery protocols have significantly reduced previously identified disparities between patients of different races. 70 Enhanced recovery after surgery protocols streamline the multidisciplinary management of patients with IBD before surgery, incorporating evidence-based practices focused on nutrition, prevention of postoperative ileus, and use of nonopioid analgesia and goal-directed fluid therapy (Table 2).…”
Section: Surgerymentioning
confidence: 99%